Recycling of parental histones preserves the epigenetic landscape during embryonic development. - Mühlen, D.; Li, X.; Dovgusha, O.; Jäckle, H.; Günesdogan, U. (Science advances, 2023)
Epigenetic inheritance during DNA replication requires an orchestrated assembly of nucleosomes from parental and newly synthesized histones. We analyzed Drosophila His[C] mutant embryos harboring a deletion of all canonical histone genes, in which nucleosome assembly relies on parental histones from cell cycle 14 onward. Lack of new histone synthesis leads to more accessible chromatin and reduced nucleosome occupancy, since only parental histones are available. This leads to up-regulated and spurious transcription, whereas the control of the developmental transcriptional program is partially maintained. The genomic positions of modified parental histone H2A, H2B, and H3 are largely restored during DNA replication. However, parental histones with active marks become more dispersed within gene bodies, which is linked to transcription. Together, the results suggest that parental histones are recycled to preserve the epigenetic landscape during DNA replication in vivo.